2015
DOI: 10.1245/s10434-015-4778-7
|View full text |Cite
|
Sign up to set email alerts
|

Complement Inhibition: A Novel Form of Immunotherapy for Colon Cancer

Abstract: Background Complement is a central part of both the innate and adaptive immune response and its activation has traditionally been considered part of the immunosurveillance response against cancer. Its pro-inflammatory role and its contribution to the development of many illnesses associated with inflammatory states implicate complement in carcinogenesis. Methods We evaluated the role of three protein inhibitors of complement—cobra venom factor, humanized cobra venom factor, and recombinant staphylococcus aur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 26 publications
(25 reference statements)
2
25
0
Order By: Relevance
“…In accord with the recent study by Downs-Canner et al (27), we also showed upregulation of the CCR5 ligand, CCL5 (RANTES) at the protein level, along with a slight, but not significant, increase in the Th2 cytokine IL-10. Increased CCL5 levels have been associated with unfavorable outcomes in some cancers (35), but they predict survival in others (36), regulating antitumor immunity (37) and synergizing with CXCR3 ligands to attract effector T cells into cutaneous metastases and inhibit tumor growth (38).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In accord with the recent study by Downs-Canner et al (27), we also showed upregulation of the CCR5 ligand, CCL5 (RANTES) at the protein level, along with a slight, but not significant, increase in the Th2 cytokine IL-10. Increased CCL5 levels have been associated with unfavorable outcomes in some cancers (35), but they predict survival in others (36), regulating antitumor immunity (37) and synergizing with CXCR3 ligands to attract effector T cells into cutaneous metastases and inhibit tumor growth (38).…”
Section: Discussionsupporting
confidence: 93%
“…The canonical proinflammatory mediator C5a has been widely implicated for a role in tumor growth, with both tumor-promoting and tumor-inhibitory effects reported, depending on tumor type, immune status of the host, and C5a levels (6)(7)(8)(9)26). Although these and other studies (27) have shown that tumor growth is reduced in the absence of C3 (which generates both C3a and C5a), the tumor-promoting effects have been attributed solely to C5a. Until now, there have been no studies investigating the role of the upstream activation fragment C3a in tumor growth.…”
Section: Discussionmentioning
confidence: 93%
“…Recent findings indicate that complement activation in the tumor microenvironment leads to tumor growth and metastasis. In vivo models using breast, lung and colon cancer cell lines showed that C5aR-mediated signaling creates a microenvironment that promotes growth through recruitment of myeloid-derived suppressor cells (MDSCs) and inhibition of anti-tumor immune responses mediated by CD8 + and CD4 + T cells (25, 2729, 36). In addition, C5a-induced inflammation is associated with promotion of angiogenesis and tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The observations that C5aR1 is required for Mreg migration/accumulation into tumors and into transplants and, as a consequence, to mediate tumor and transplant survival illustrate commonality of mechanism despite distinct pathophysiologic contexts. Complement component C3 has been separately shown to be important in the differentiation of MDSCs, an effect that has not been attributed to C5aR1. While we have not formally documented the source of C5a in this system, we speculate, based on our previous work, that it derives from recipient plasma and/or recipient immune cell–produced complement …”
Section: Discussionmentioning
confidence: 99%